Fx=4x+6

Simple and best practice solution for Fx=4x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Fx=4x+6 equation:


Simplifying
Fx = 4x + 6

Reorder the terms:
xF = 6 + 4x

Solving
xF = 6 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-4x + xF = 6 + 4x + -4x

Combine like terms: 4x + -4x = 0
-4x + xF = 6 + 0
-4x + xF = 6

Reorder the terms:
-6 + -4x + xF = 6 + -6

Combine like terms: 6 + -6 = 0
-6 + -4x + xF = 0

The solution to this equation could not be determined.

See similar equations:

| 2x+3y=8fory | | 2x-5+35+90=180 | | 3x^2-14=x^2+3x | | 8x/8=24/.5 | | 2(4n+64)=24n | | 2(n+27)=11n | | x+-3=4.5 | | 8p-5p+3=37p-1 | | 7q+14-5g=-8 | | 5(x+4)+8=33 | | 4(2x+1)=5x+3x+3x+9 | | 6(3r+3)+4r-4= | | 9(x-4)-2x=5(x-2) | | 6/7x-4/5=(5x+3)/2 | | x^50=.2 | | 2(12.3)=n+8.7 | | H=5/2(3.14)m^3c | | (6/7x)-4/5=(5x+3)/2 | | 2(6n)=48 | | 5x+6x-36=54-7x | | 8c-(5x-22)=49 | | 23-2X= | | 4n+2n=-4 | | 2x-3(2x+5)=7x-12 | | -07x=-6.3 | | 0.02-0.3= | | y^2-4x+2y+5=0 | | h(x)=-5x^2-20 | | 0=x^2-8x+64 | | 5x1/2-8=7 | | 5a^2-10a-84=-9 | | 3(x-1)+5x=24 |

Equations solver categories